2020
DOI: 10.3390/jcm9123798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spirituality, Knowledge, Attitudes, and Practices toward Anxiety Regarding COVID-19 among the General Population in INDONESIA: A Cross-Sectional Study

Abstract: Background: Currently, the determinants of anxiety and its related factors in the general population affected by COVID-19 are poorly understood. We examined the effects of spirituality, knowledge, attitudes, and practices (KAP) on anxiety regarding COVID-19. Methods: Online cross-sectional data (n = 1082) covered 17 provinces. The assessment included the Daily Spiritual Experiences Scale, the Depression, Anxiety, and Stress Scale, and the KAP-COVID-19 questionnaire. Results: Multiple linear regression revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
77
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(88 citation statements)
references
References 61 publications
4
77
1
6
Order By: Relevance
“…Particularly, 215,059 people were infected in East Java with 11,707 fatalities and obtained the 4 th rank in Indonesia (Gugus Tugas Percepatan Penanganan COVID-19, 2021). This situation is in line with the previous literature established that inadequate health practices among Indonesian citizens (Rias et al, 2020) or low public behaviors of citizens regarding the COVID-19 pandemic (Jose et al, 2021), complicating efforts to prevent the spread of this pandemic. Consequently, the containment of the COVID-19 pandemic must continue to rely on personal health behaviors control to decline the exposure (Bechard et al, 2021;Jose et al, 2021).…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Particularly, 215,059 people were infected in East Java with 11,707 fatalities and obtained the 4 th rank in Indonesia (Gugus Tugas Percepatan Penanganan COVID-19, 2021). This situation is in line with the previous literature established that inadequate health practices among Indonesian citizens (Rias et al, 2020) or low public behaviors of citizens regarding the COVID-19 pandemic (Jose et al, 2021), complicating efforts to prevent the spread of this pandemic. Consequently, the containment of the COVID-19 pandemic must continue to rely on personal health behaviors control to decline the exposure (Bechard et al, 2021;Jose et al, 2021).…”
supporting
confidence: 88%
“…Preventing and or reducing the spread of infection is accomplished by practical personal care measures, which involved washing hands, wearing a mask, and required standard social distancing that could mitigate the COVID-19 transmission (Rias et al, 2020;Bechard et al, 2021;Muslih et al, 2021). Notably, these activities should be encouraged and viewed as primary preventative measures targeting COVID-19 immediately to protect its transmission (Muslih et al, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies examining COVID-19 related knowledge have been conducted among Indonesian populations. However, those studies' respondents were non-health students [11], [12] and the general public [13], [14]. To the best of our knowledge, research showed the relationship between knowledge and quality of life in health and non-health students has not been carried out before.…”
Section:  Issn: 2252-8806mentioning
confidence: 99%
“…It contained three main sections that address questions on the fear of COVID-19, Spirituality, and stigmatization. The online google form has been used previously by many researchers on studies of this nature ( Lucchetti et al., 2020 ; Rias et al., 2020 ; Kowalczyk et al., 2020 ). The study was conducted in Lagos, Ogun, Oyo, Osun in the southwest part of Nigeria.…”
Section: Methodsmentioning
confidence: 99%